Comparative Analysis of Verbs of Motion in Uzbek and English Languages (Texas Journal of Philology, Culture and History, 2023)
This article discusses the semantic issues of verbs of motion in English and Uzbek languages. At the same time, a comparative analysis of the verb of motion of the English and Uzbek languages is carried out in the space of a particularly relevant microfield, which specifically indicates the semantic parameters of the verbs of motion, as well as involving the application of a variety of methods of linguistic analysis.